Hybrid Learning, Digital Ethics, and Ecopedagogy: Reconstructing Teacher Competencies for Sustainable Futures - Peter Zena; Hasna Laysa (PT Mutiara Bustan Ilmu, 2025)
The transformation of 21st-century education is characterized by the rapid adoption of hybrid learning, the increasing importance of digital ethics, and the urgent call for sustainability-oriented education through ecopedagogy. This study aims to reconstruct teacher competencies by integrating these three critical components to build a sustainable educational future. Employing a qualitative approach through critical literature review and in-depth interviews with education practitioners, this research identifies core competencies required of teachers in the digital age: pedagogical adaptability in hybrid environments, ethical digital literacy, and ecopedagogical awareness. The findings indicate that a synergistic integration of technology, ethical values, and ecological consciousness can foster a new paradigm in teacher professional development. The study's implications suggest the need for holistic and future-oriented teacher training programs and educational policies that are responsive to global challenges. Ultimately, teachers are positioned not only as facilitators of learning but also as transformative agents for inclusive, ethical, and sustainable futures